THE IMPACT OF NON-LINGUISTIC ELEMENTS ON PHONOSTYLISTIC CHANGES (American Journal of Research in Humanities and Social Sciences, 2023)
Modern linguistics, amidst its focus on internal linguistic quandaries, delves into the intricacies of language communication. Specifically, it scrutinizes the interplay between language and its users - be it the speaker or listener - while also exploring the nexus between language and the communication process, encompassing environmental and contextual factors. Furthermore, it delves into the intersections of language with logic, philosophy, and the comprehension of the world. Notably, contemporary linguistic scholarship is earnestly engaging in an exploration of the interconnections between language and culture. Presently, there exists a significant emphasis on linvoculturological research - a domain dedicated to scrutinizing the triad of language, humanity, and culture, meticulously probing the dynamics between culture and language. Within this context, this study ardently delves into the nuances of phonostylistics, an emergent frontier in linguistics that offers a fresh perspective on phonetic phenomena.